Empowerment Through Mystical Experiences in Islam: A Literature Study on Muhammad PBUH’s First Revelation of Islam. - Bintari, Dini Rahma (Unisia, 2018)
This paper discusses how empowerment can be triggered by mystical experiences, by focusing on mystical experience of the first revelation of Islam to Muhammad PBUH. Only few literature on empowerment in mainstream psychology, specifically discuss how empowerment can be achieved through personal mystical or spiritual experiences. Transpersonal studies give explanations of human mystical experiences and extra sensory perceptions. Chronological analysis of the first revelation showed how the mystical experience empowered Muhammad. First, mystical experience is empowerment. Second, mystical experiences can become an effective and an efficient trigger for empowerment in daily life if understood correctly; and affirmed with social support. Third, spiritual awakening can unfold into intrapersonal, interpersonal and behavioral empowerment if the person contemplates about the experience, and implement it to benefit others.